Acceptance and Commitment Therapy Preceded by Attention Bias Modification on Residual Symptoms in Depression: A 12-Month Follow-Up - Østergaard, Tom; Lundgren, Tobias; Rosendahl, Ingvar; Zettle, Robert D.; Jonassen, Rune; Harmer, Catherine J.; Stiles, Tore C.; Landrø, Nils Inge; Haaland, Vegard Øksendal (Frontiers in Psychology, 2019)
Depression is a highly recurrent disorder with limited treatment alternatives for reducing risk of subsequent episodes. This study investigates the effect of group-based acceptance and commitment therapy (ACT) following attention bias modification (ABM) on residual symptoms of depression over a 12-month follow-up. This multisite study consisted of two phases. In phase 1, participants with a history of depression, currently in remission (N = 244), were randomized to either receive 14 days of ABM or a control condition. In phase 2, a quasi- experimental design was adopted, and only participants from the Sørlandet site next received an 8-week group-based ACT intervention. Self-reported and clinician-rated depression symptoms were assessed at baseline, immediately after phase 1 and at 1, 2, 6, and 12 months after the conclusion of phase 1. At 12-month follow-up, participants who received ACT exhibited fewer self-reported and clinician-rated depressive symptoms. There were no significant differences between ACT groups preceded by ABM or a control condition. Group-based ACT successfully decreased residual symptoms in depression over 12 months, suggesting some promise in preventing relapse. ABM did not augment group-based ACT.